2015
DOI: 10.1002/elps.201500086
|View full text |Cite
|
Sign up to set email alerts
|

Variations of secretome profiles according to conditioned medium preparation: The example of human mesenchymal stem cell‐derived adipocytes

Abstract: One challenging point in analyzing cellular secretome collected as conditioned medium is cross-contamination by cell culture media components, especially bovine serum proteins. A common approach for serum removal is to wash the cells, an alternative is to grow cells using serum-free conditions. Given that the sample processing may influence the phenotype of cells and thus the secretome, it is important to establish the optimal protocol for each cell type. In this study, we compared two methods for preparing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The phenomenon that mesenchymal stem cells could improve distal injury organ healing without cell migration and cell differentiation indicates that the cell exosomes play an important role in tissue and organ repair [ 5 7 ]. In addition to cell differentiation and proliferation, the secreted proteins also represent an important extension of the stem cells' function [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon that mesenchymal stem cells could improve distal injury organ healing without cell migration and cell differentiation indicates that the cell exosomes play an important role in tissue and organ repair [ 5 7 ]. In addition to cell differentiation and proliferation, the secreted proteins also represent an important extension of the stem cells' function [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We employed protocols without FBS supplement because it has been shown that low serum content conditions in combination with reduced biomechanical input lower the fibroblast activation state [ 24 ]. Moreover, the large number of proteins present in serum hampers in-depth proteomic analysis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, several authors highlighted the urgency to properly characterize secretomes composition and relate the secreted proteins to their corresponding regenerative functions. 15,18,19,71 Variations in benefits can arise due to many factors such as tissue source, 13 culture conditions and materials used in conditioned media production, 19,20,22,72 secretomes isolation methods 19 and protein detection methods 71 amongst many others. UC-MSCs reportedly produce proteins with a strong correlation to skin renewal as compared with ADSC or BM-MSCs.…”
Section: Efficacy Of Secretomesmentioning
confidence: 99%